Immunosuppressive treatment results in patients with primary IgA nephropathy in Turkiye; the data from TSN-GOLD working group - Aysegul Oruc; Abdullah Sumnu; Aydın Turkmen; Taner Basturk; Egemen Cebeci; Kenan Turgutalp; Hakkı Cetinkaya; Müge Uzerk Kibar; Nurhan Seyahi; Erhan Tatar; Metin Ergul; Ülver Derici; et al. (Renal Failure)
Background Immunoglobulin A (IgA) nephropathy (IgAN) treatment consists of maximal supportive care and, for high-risk individuals, immunosuppressive treatment (IST). There are conflicting results regarding IST. Therefore, we aimed to investigate IST results among IgAN patients in Turkiye.Method The data of 1656 IgAN patients in the Primary Glomerular Diseases Study of the Turkish Society of Nephrology Glomerular Diseases Study Group were analyzed. A total of 408 primary IgAN patients treated with IST (65.4% male, mean age 38.4 ± 12.5 years, follow-up 30 (3–218) months) were included and divided into two groups according to treatment protocols (isolated corticosteroid [CS] 70.6% and combined IST 29.4%). Treatment responses, associated factors were analyzed.Results Remission (66.7% partial, 33.7% complete) was achieved in 74.7% of patients. Baseline systolic blood pressure, mean arterial pressure, and proteinuria levels were lower in responsives. Remission was achieved at significantly higher rates in the CS group (78% vs. 66.7%, p = 0.016). Partial remission was the prominent remission type. The remission rate was significantly higher among patients with segmental sclerosis compared to those without (60.4% vs. 49%, p = 0.047). In the multivariate analysis, MEST-C S1 (HR 1.43, 95% CI 1.08–1.89, p = 0.013), MEST-C T1 (HR 0.68, 95% CI 0.51–0.91, p = 0.008) and combined IST (HR 0.66, 95% CI 0.49–0.91, p = 0.009) were found to be significant regarding remission.Conclusion CS can significantly improve remission in high-risk Turkish IgAN patients, despite the reliance on non-quantitative endpoints for favorable renal outcomes. Key predictors of remission include baseline proteinuria and specific histological markers. It is crucial to carefully weigh the risks and benefits of immunosuppressive therapy for these patients.